Large trigeminal schwannoma of the infratemporal fossa: Evaluation of neoangiogenesis in this rare neoplasm. Issue 9 (10th September 2012) - Alafaci, Concetta; Caffo, Maria; Barresi, Valeria; Cutugno, Mariano; Pino, Maria A.; Granata, Francesca; De Ponte, Francesco S.; Salpietro, Francesco M.; Tomasello, Francesco; Andersen, Peter
Abstract Background Trigeminal schwannomas are uncommon intracranial tumors. Extracranial trigeminal schwannomas in the infratemporal fossa are rare. Methods We present a case with a clinical history of facial pain. MRI and CT scans showed a mass arising from the infratemporal fossa extending into the intracranial space. Results We performed a combined neurosurgical and maxillofacial approach with preoperative endovascular embolization. Complete removal of the parasellar component was achieved with a minimal extracranial neoplastic residual. High microvessel density, reflecting intense neoangiogenesis, was detected through the immunohistochemical staining with endoglin. Conclusions Due to the unique development pattern of trigeminal schwannoma involving multiple intracranial fossae and extracranial compartment, we chose a combined neurosurgical and maxillofacial approach with preoperative embolization of the tumor. Immunohistochemical findings suggest that the extensive growth observed may be related to an intense neoangiogenesis, opening the perspective to novel therapeutic options based on the inhibition of neoangiogenesis. © 2012 Wiley Periodicals, Inc. Head Neck, 2013